Learning Lessons for Evaluating Complexity Across the Nexus: A Meta-Evaluation of Environmental Projects - William Robert Sheate; Clare Twigger-Ross; Liza Papadopoulou; Rolands Sadauskis; Owen White; Paula Orr; Richard Eales (Journal of MultiDisciplinary Evaluation)
Background: A major gap in environmental policy making is learning lessons from past interventions and in integrating the lessons from evaluations that have been undertaken. Institutional memory of such evaluations often resides externally to government, in evaluation practitioner contractors who undertake commissioned evaluations on behalf of government departments.